Financial bootstrapping: external financing dependency alternatives for SMEs - Maria Rio Rita (Jurnal Ekonomi dan Bisnis, 2019)
The sensitivity of external financing is the main issue in developing small and medium-sized enterprises (SME) in general. A similar problem is also experienced by several batik small and medium enterprises in Central Java, Indonesia. This research strives to explore the creative alternative strategies done by batik micro, small, and medium enterprises to reduce the dependence on external capital. The samples were chosen based on a purposive sampling method in three Central Java regions, namely Pekalongan Regency, Rembang Regency, and Surakarta Municipality. The data were then analyzed using a quantitative and qualitative descriptive approach. These research findings reveal that there are variations in the bootstrapping financing method; as well as financing profiles of each in the three regions that reveal the dynamics of business funding. Referring to the description of alternative funding patterns carried out by entrepreneurs, the bootstrapping strategy can be grouped into six (6) types based on the available resources. Batik entrepreneurs can overcome their financial problem by applying bootstrapping methods, so that businesses can operate properly.